2010
DOI: 10.4269/ajtmh.2010.09-0302
|View full text |Cite
|
Sign up to set email alerts
|

Rubella Seroepidemiology and Catch-up Immunization among Pregnant Women in Taiwan: Comparison between Women Born in Taiwan and Immigrants from Six Countries in Asia

Abstract: Abstract. Rubella vaccination in Taiwan started in 1986; mass vaccination was introduced into the national immunization program in 1992. In recent years, 17-31% of all marriages in Taiwan have been between Taiwanese men and foreign women. The aim of this study was to analyze rubella seroepidemiology and the rate of catch-up immunization in women. We recruited 10,089 pregnant women, including 1,920 immigrants, who had received prenatal examinations during 1999-2006. The rates of seronegativity among global, Tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
(13 reference statements)
2
11
1
2
Order By: Relevance
“…Our finding that 28.9% of pregnant women were susceptible to rubella is consistent with that from these reports, in which 24-36% of pregnant women were susceptible [19,21]. In another study investigating 45 developing countries before RCV had been used, the susceptibility in WCBA was generally 15-20% but exceeded 25% in 12 countries [22].…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that 28.9% of pregnant women were susceptible to rubella is consistent with that from these reports, in which 24-36% of pregnant women were susceptible [19,21]. In another study investigating 45 developing countries before RCV had been used, the susceptibility in WCBA was generally 15-20% but exceeded 25% in 12 countries [22].…”
Section: Discussionsupporting
confidence: 91%
“…We found that among all the primiparous women, the seronegativity was 6.5% (95% CI, 6.1 to 6.9%), and the average GMT was 65.9 IU/ml (95% CI, 64.7 to 67.1 IU/ml). Relative to the rubella virus seronegativity rates among local women of childbearing age who were born after the onset of the vaccination program in different areas of Taiwan (11,21,24), the average seronegativity from the present study was higher than those in northern and central-southern Taiwan (4.9 and 4.0%) but lower than that in southern Taiwan (7.9%). In comparing the seronegativity of rubella virus antibodies in Taiwan nationwide to the results from a previous study (12), the susceptible rate found in the current study was slightly higher than that for pregnant women born during 1971 to 1975 (6.5 versus 6.1%) and lower than that for those born after 1976 (6.5 versus 7.2%).…”
Section: Discussioncontrasting
confidence: 69%
“…[17][18][19] Therefore, to eliminate rubella infection, the postpartum immunization should be launched and vaccination should be provided to the susceptible women, either native or immigrant, before they are discharged from hospitals. 20 In Taiwan, almost all women have prenatal checkups. The bills are paid by NHI, regardless of whether childbirths take place in hospitals or at obstetrics clinics.…”
Section: Discussionmentioning
confidence: 99%